Prevalence of Urinary Schistosomiasis Among Children Attending Some Selected Primary Schools In Zangon Shanu Zaria - Sulaiman, M.A.; Musa Hassan Muhammad; Hussaini, I.M.; Bobzom, B. S.; Ibrahim A. (UMYU Journal of Microbiology Research)
Urinary schistosomiasis is endemic in Nigeria, and continues to pose public health challenges, especially among the inhabitants of rural areas. Urinary schistosomiasis occurs in all the states of Nigeria with the highest infection rate among school age children between 6 to 17 years. This study aimed at determining the prevalence of Schistosoma heamatobium infection among primary school pupils in Zangon shanu Zaria, and its relationship with some physicochemical indices of urine, studied through urinalysis. A total of one hundred and fifty (150) urine samples (75 samples from each of the two schools) were collected and examined using sedimentation technique. The parameters examined include symptoms of the disease as haematuria (presence of blood in urine), proteinuria (presence of protein in the urine) and dysuria (painful urination). The associations of risk and demographic factors with the disease were also examined, using structured questionnaire. An overall prevalence of 5.33% with 7.5% among male and 1.8% among female was obtained. The age group 13-16 years has the highest prevalence of 9.8%among the rest. The research also revealed the statistical association of shistosomiasis with haematuria, proteinuria and dysuria(p<0.05) among the subjects. The outcome of the research is an indication that schistosomiasis remained endemic in the study area, and hence recommended that control measures should be applied with a greater vigor.